Google Form as an Online Assessment Tool to Improve the Students’ Vocabulary Mastery - Rizal Rinaldi; Wiyaka Wiyaka; Entika Fani Prastikawati (STAIN Sultan Abdurrahman Kepulauan Riau, 2022)
Digital learning has existed since 2000, but in that year digital learning was not as advanced as in 2020. In 2020, digital learning has taken place in the field of education because today's technology can be accessed very easily. However, the problem that often arises is that teachers do not use internet digital media for the learning and assessment process. To address the existing gaps, this study is trying to investigate the current implementation of Google Form as online vocabulary assessment in English teaching and compare to the traditional vocabulary assessment. To reach that purpose, this study applied quasi-experimental study design. The population of the study class VIII Students of SMP N 9 Semarang in 2021/2022. The writers took two classes as control class and experimental class. There are two types of instrument tests given, namely pre-test and post-test. The result of the study reveals that there is a significant difference in the vocabulary mastery between those taught using Google Form as online vocabulary mastery and those taught using traditional vocabulary assessment. This is proved by the t-test result in which its value is greater than the t-table. This result implies that Google Form can be an alternative vocabulary assessment during the online and blended English teaching and learning process.